Combined effect of fabomotizol and the compound ALM-802 on atrial depolarization in a translational model of alcoholic cardiomyopathy in rats - S. L. Smirnova; I. M. Roshchevskaya; V. V. Barchukov; I. B. Tsorin; S. A. Kryzhanovskii (LLC "Publisher OKI", 2023)
Relevance. Alcoholic cardiomyopathy (ACMP) is the leading cause of mortality in chronic disease, which is largely associated with an increased risk of developing malignant diseases of the cardiovascular disease. Search for new drugs, including those exhibiting pronounced antiarrhythmic activity, supposed relevance. Objective. To study the effect of combination therapy with fabomotizole and ALM-802 on atrial depolarization in a translational model of alcoholic cardiomyopathy in rats. Methods. The sequence of depolarization of the atrial epicardium was studied in rats in a translational model of alcoholic cardiomyopathy, which received a combination of fabomotizole and compound ALM-802 daily for 28 days after the end of 24 weeks of alcoholization, or pyrogen-free water intraperitoneally. Results. As a result of the 28-day combined action of fabomotizole and the compound ALM-802 in animals with alcoholic cardiomyopathy, additional areas of early activation in the area of lacunae of the pulmonary veins that form during the 24-week period of alcoholization disappear, the risk of atrial arrhythmias is minimized, and sequential propagation.